Seasonality of plasma tryptophan and kynurenine in pregnant mothers with a history of seasonal affective disorder: Vulnerability or adaptation?. (8th August 2020) - Levitan, Robert D.; Sqapi, Maria; Atkinson, Leslie; Murphy, Kellie; Levitt, Anthony; Bocking, Alan; Post, Martin; Knight, Julia A.; Matthews, Stephen G.
Abstract: Objectives: Maternal-foetal tryptophan metabolism plays multiple roles in neurodevelopment and immunomodulation across pregnancy. Tryptophan and the immune system are both influenced by the seasons of the year. We thus compared tryptophan and kynurenine levels in subgroups of pregnant women defined by maternal seasonality and season-of-conception (SoC). Methods: Maternal plasma samples taken at 9–15 and 23–29 weeks of pregnancy were analysed in 47 women with historical full or sub-syndromal Seasonal Affective Disorder (SAD) and 144 pregnant controls. Repeated measure ANCOVAs compared tryptophan and kynurenine levels in the two study groups over the two pregnancy sampling times, using SoC as a moderator. Results: Significant differences in both plasma tryptophan and kynurenine were found across the eight subgroups defined by maternal seasonality and SoC. These results were independent of the state of depression. Conclusions: Pregnant women with a history of full or sub-syndromal SAD exhibited a different pattern of plasma tryptophan and kynurenine across the seasons compared to control mothers, independent of current mood state. Follow-up of the children will determine the implications of these findings for neurodevelopment and psychiatric risk. Maternal seasonality and SoC may be important considerations when studying tryptophan and its metabolites in human pregnancy and foetal brain development.